Corporate Governance and Organization Performance in Non-profit Organizations: Evidence from the UK Charities - DU, MINGZHU (2018)
This paper explores the relationship between the internal corporate governance mechanism and the charity performance in the UK. Based on agency theory and resource dependency theory, this study quantifies five characteristics of the board, including the board size, board tenure, board activity, board committees, and board leadership. The charitable commitment, fundraising expense percentage, and charitable income reliance are efficiency indicators. This study employs 121 charities out of top 300 charities in the UK and selects related data from 2013-2017. Descriptive and OLS regression methods are used to analyse the statistics. The findings suggest the board size and tenure are positively related to the charitable income reliance ratio showing that the large board with long tenure could generate more resources and have positive impacts on the efficiency. Besides, the results present that the separation of leadership roles improves efficiency by mitigating agency problem in the charity. In regard to functional committees including the audit committee and the finance committee, significant inverse relationships are presented with the charity performance. Together with the same results of the board meetings, the ineffectiveness of the board of trustees may be presented. Alternatively, the board activity and functional committees may be used to respond to the poor performance of charities. The presence of the nomination committee is not significantly related to the charity performance. Due to inadequate observations and insufficient corporate governance variables, future studies are suggested employing a larger sample size and more representative variables for deeper investigation.